Study effect of additive on PVDF membrane for CO2/N2 gas separation process - Siti Farah Amirah, Ahmed (2015)
Flat sheet asymmetric membranes were produced from homogenous solution of Poly(vinylideneflouride) (PVDF) via phase inversion method using N-methyl-2-pyrrolidone (NMP) as the solvent and Lithium Chloride (LiCl) as an additive. The effect of addition of different ratio of LiCl in the casting solution on the membrane properties and performance were studied. The morphology and cross section of the produced membranes were observed by Scanning Electron Microscope (SEM). Then, the membranes were tested for chemical analysis to define the presence of LiCl in the membrane by using Fourier Transform Infrared (FTIR) spectroscopy. The permeation performances of the membranes were evaluated in terms of permeability and selectivity of the membranes in separating the gaseous mixture by using single gas permeation test. The addition of LiCl into the casting solution definitely improved the morphology and structure of the membrane. The macrovoid formation was suppressed and very fine pores were formed at higher LiCl content. Increasing the LiCl content significantly increased the selectivity of the PVDF membrane to separate the CO2/N2 gases but decreased the amount of the gases that passed through the membrane.